Climatic and tectonic controls on strath terraces along the upper Weihe River in central China. Issue 3 (November 2016) - Gao, Hongshan; Li, Zongmeng; Ji, Yapeng; Pan, Baotian; Liu, Xiaofeng
Abstract: The Weihe River in central China is the largest tributary of the Yellow River and contains a well-developed strath terrace system. A new chronology for the past 1.11 Ma for a spectacular flight of strath terraces along the upper Weihe River near Longxi is defined based on field investigations of loess—paleosol sequences and magnetostratigraphy. All the strath terraces are strikingly similar, having several meters of paleosols that have developed directly on top of fluvial deposits located on the terrace treads. This suggests that the abandonment of each strath terrace by river incision occurred during the transition from glacial to interglacial climates. The average fluvial incision rates during 1.11—0.71 Ma and since 0.13 Ma are 0.35 and 0.32 m/ka, respectively. These incision rates are considerably higher than the average incision rate of 0.16 m/km for the intervening period between 0.71 and 0.13 Ma. Over all our results suggest that cyclic Quaternary climate change has been the main driving factor for strath terrace formation with enhanced episodic uplift.